A comparative study between epoxy and vinyl ester CF-SMC for high volume automotive composite crash structures. (15th July 2020) - Gupta, Jaipal; Reynolds, Neil; Chiciudean, Teodor; Kendall, Kenneth
Abstract: Epoxy- and vinyl ester-based carbon fibre reinforced sheet moulding compounds (CF-SMCs) were industrially processed and impact tested to characterise their impact energy absorption performance. Particularly, thin-walled CF-SMC components were manufactured via a high volume compression moulding process, and were subjected to both ~9 m/s and ~13 m/s dynamic impacts with kinetic energies of ~3.3 kJ and ~6.6 kJ respectively. The mass-specific energy absorption (SEA) for epoxy-based CF-SMC ranged from 50 to 60 J/g whereas the SEA for vinyl ester material ranged from 24 to 29 J/g. In addition, the effect of the manufacturing process and the resultant reinforcement architecture on the energy absorption properties was investigated. Epoxy CF-SMC components were manufactured using conventional SMC flow forming and using 'pre-formed' near-net shape blanks (low/zero flow condition) and their performance compared. Local microstructure and fractography analyses were conducted for each sample type to explain the observed differences in performance between the individual CF-SMC and manufacturing systems.